2022
DOI: 10.1038/s41591-022-01721-6
|View full text |Cite
|
Sign up to set email alerts
|

Antibody responses and correlates of protection in the general population after two doses of the ChAdOx1 or BNT162b2 vaccines

Abstract: Antibody responses are an important part of immunity after Coronavirus Disease 2019 (COVID-19) vaccination. However, antibody trajectories and the associated duration of protection after a second vaccine dose remain unclear. In this study, we investigated anti-spike IgG antibody responses and correlates of protection after second doses of ChAdOx1 or BNT162b2 vaccines for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in the United Kingdom general population. In 222,493 individuals, we found signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
180
2
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(258 citation statements)
references
References 48 publications
(54 reference statements)
33
180
2
5
Order By: Relevance
“…Current diagnostic assays for anti-RBDwt titers are not interchangeable, even when results are converted to BAU/ml 39 . Thus, the median titers reported for sera collected from healthy individuals after two doses of mRNA vaccines vary by more than seven-fold (959 to 7812 BAU/ml) 1,2,6,7 . Variation in samples used as standards in different assays and laboratories is likely to be a contributing factor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current diagnostic assays for anti-RBDwt titers are not interchangeable, even when results are converted to BAU/ml 39 . Thus, the median titers reported for sera collected from healthy individuals after two doses of mRNA vaccines vary by more than seven-fold (959 to 7812 BAU/ml) 1,2,6,7 . Variation in samples used as standards in different assays and laboratories is likely to be a contributing factor.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the neutralization titers corresponding to 90% vaccine efficacy against symptomatic COVID-19 varied by more than ten-fold in two clinical trials 1,2 . Titers reported for binding antibodies (binding antibody units per milliliter, BAU/ml) after two doses of mRNA vaccines vary by seven-fold 1,2,[6][7][8] . There is therefore an unmet need for standardized high-throughput assays that can be used to monitor bindingand neutralizing antibodies against different SARS-CoV-2 variants at the individual level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower and upper detection limits of the assay were 4.81 BAU/ml and 2080 BAU/ml, respectively. Previous studies have suggested that antibody levels >94 BAU/mL after two BNT162b2 vaccine doses associated with 67% of individuals being protected against infection with the delta variant [ 8 ], and antibody levels >300 BAU/mL after two mRNA-1273 doses associated with 90% vaccine efficacy. We have evaluated the vaccine response in this cohort in relation to those tresholds [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…The infectivity, immune escape ability and pathogenicity of different mutants are different, which may cause confusion in the evaluation of vaccine effectiveness. Third, this analysis fails to account for potentially important confounding factors, including previous COVID-19 infection, populations with more sustained immune protection and possibly greater emphasis on personal protection 4 , such as wearing masks, that can influence the assessment of vaccine effectiveness. Fourth, the novel coronavirus vaccine may have cross-protection against other pathogens, leading to the conclusion that the vaccine protection effect is low.…”
mentioning
confidence: 99%